Consumer responses towards the 4ps marketing strategies in the conflict affected areas of Sri Lanka: a grounded theory approach - Shivany, S.; Velnampy, T.; Kajendra, K. (University of Jeyewardenepura, 2015)
In the post-war era, local firms are facing stiff competition from foreign brands. In order to compete successfully they need to develop new marketing strategies on post-war perspective. At the same time, they also need to focus on all the marketing activities from the consumer’s perspectives. During war, consumers were more conscious on the product accessibility, and did not consider the other aspects in the brands, but in the post-conflict marketing environment they expect good value for the money which they spent on the product Extent research on marketing strategies lacks in theory based frame work that explicate what marketing strategies are appropriate for the war/conflict affected places. The present study explored marketing strategies, appropriate to the unique context. Using grounded theory methodology data were collected, through 5 focus group discussions and 25 interviews with the consumers in the Northern Province of Sri Lanka. Theoretical sampling technique is used to select the appropriate respondents; Data were collected until the data saturation was arrived. 89 initial codes were identified from the initial coding viaNvivo (version 09) software. From the axial coding and substantial coding 11 categories were found. Marketers adopt 15 strategies to reach the consumers in the conflict affected places. Consumers prefer 05 strategies, such as social responsibility, cultural match, ethical marketing, employee’s behavior, and infrastructure development as the best from the 15 strategies. Ethical marketing strategy is needed in the conflict affected places. Findings show that, consumers in the conflict affected places expect ethical behavior in all aspects of marketing activities.
Keywords: Post war marketing environment; Marketing strategies; Grounded theory